THE MEANING OF ACCOUNTING EDUCATION. - Littleton, A. C. (The Accounting Review, 1942)
Abstract Education for a career in accountancy, then, as in all education, has the objective of preparing individuals to act in certain ways with understanding. It, too, is a union of teaching and learning, combined in differing proportions. A complete education will take more time than an incomplete education. An in- complete education can be accomplished with a minimum of formal teaching; a more complete preparation usually leans heavily upon the vicarious processes of learning. Accounting is used in the social interest as an instrument of regulation of business; uniform systems of accounts and reports have been required in some cases; audits may have been prescribed; professional accountants are examined and licensed; accounting provisions are increasing in corporation laws. Such an appreciation approach would seem to be a very appropriate one in many educational situations. Yet this approach is seldom found among the college offerings. Intensely specialized programs of study undoubtedly have a place. Classes after hours and correspondence courses often serve a very useful purpose in this connection. But intensive specialization works under very definite limitations. If used to supplement prior general education, some disadvantage may appear because prior and present subject matter are not well interwoven.